Identification of lactoferrin and glutamate receptor‐interacting protein 1 in bovine cervical mucus: A putative marker for oestrous detection. (25th November 2016) - Lee, WY; Park, MH; Kim, KW; Song, H; Kim, KB; Lee, CS; Kim, NK; Park, JK; Yang, BC; Oh, KB; Im, GS; Chung, HJ
Contents: Accurate detection of oestrus is important for artificial insemination. The aim of this study was to identify oestrous‐specific bovine cervical mucus proteins that could be used to determine the optimal time for artificial insemination. Non‐oestrous and controlled internal drug release (CIDR)‐induced oestrous‐stage mucus proteins were purified and subjected to surface‐enhanced laser desorption/ionization time‐of‐flight mass spectrometry, sodium dodecyl sulphate polyacrylamide gel electrophoresis and MALDI‐TOF/TOF. Among differentially expressed proteins, lactoferrin (LF) and glutamate receptor‐interacting protein 1 (GRIP1) showed a twofold increase during the CIDR‐induced oestrous stage compared to the levels in non‐oestrous stage in bovine cervical mucus. The RT‐PCR, Western blotting and immunohistochemistry results showed that LF and GRIP1 expression was significantly increased during the oestrous stage in the uterus. This study demonstrated that bovine LF and GRIP1 exist during the oestrous stage, but not during the non‐oestrous stage, suggesting that cervical mucus LF and GRIP1 are useful oestrous detection markers in cattle.